The Main Character Analysis in “The Diamond Necklace” by Guy De Maupassant - Ika Handayani; Eri Rahmawati (Journal of English Language Teaching and Cultural Studies, 2023)
The present study aims to describe the inferiority feeling and striving for superiority aspects of the main character, "Mathilde Loisel" in the short story "The Diamond Necklace" by a French author, Guy De Maupassant. The data source of this research is primarily taken from the sentences containing dialogues and conflicts experienced by the main character, Mathilde Loisel in the short story of "The Diamond Necklace" by Guy De Maupassant. While the secondary data were taken from any references related to the theory of literature, Alfred Adler’s Individual Psychology, and related researches. This research uses descriptive qualitative method and uses literature and documentation as data collection method. The results of the data analysis showed that the main character Mathilde Loisel struggled from her inferiority (her shortcomings) to her superiority using various forms of complex compensation and superiority. The results of analysis showed that this short story deserves to be discussed in literature study since there are many positive values that can be learned for individual character building.Keywords:  main character; psychology of literature; Individual Psychology; inferiority; superiority